ANALISIS SEMIOTIK DALAM PUISI “BURUNG HITAM” KARYA W.S RENDRA - Devannia Putri Rizky; Wikanengsih Wikanengsih; Via Nugraha (IKIP Siliwangi, 2021)
Poetry is an expression of the soul through beautiful words. Poetry can motivate any reader who wants to know the meaning of the meaning implied in a poem through analysis. With this, the authors are interested in conducting research by analyzing the poem by W.S Rendra, entitled